Potensi Metabolit Sekunder Trichoderma spp. untuk Mengendalikan Penyakit Vascular Streak Dieback (VSD) pada Bibit Kakao - Rita Harni; Widi Amaria; Syafaruddin Syafaruddin; Anis Herliyati Mahsunah (Pusat Penelitian dan Pengembangan Perkebunan, 2017)
Trichoderma spp. is a beneficial microbe that produces bioactive molecules (secondary metabolites) containing antibiotics, enzymes, hormones, as well as toxins, which play an important role in plant diseases biocontrol. The research aimed to determine the potential of secondary metabolite Trichoderma spp. to control vascular streak dieback disease in cacao seedlings. The research was conducted in Plant Protection Laboratory of Indonesian Industrial and Beverage Crops Research Institute (IIBCRI) and farmers' garden in Balubus village, Lima Puluh Kota, West Sumatera, from April to August 2016. The research used a complete randomized design of 7 treatments using 5 replications, each treatment with 5 plants. The treatment was a secondary metabolite of T. virens LP1, T. hamatum LP2, T. amazonicum LP3, T. atroviride JB2, and T. viride PRD, control (no secondary metabolite), and chemical fungicide as comparison. The 3 months old cacao seedlings were treated with secondary metabolite of Trichoderma spp. by spraying the metabolite suspension throughout the leaf surface. The secondary metabolite applied once a week for 6 times. C. theobromae inoculation was conducted naturally by placing cacao seedlings under a cacao tree infected with VSD. Observations were incubation period, VSD intensity, and growth of cacao seedlings. The results showed that secondary metabolites potentially utilized for controlling VSD in cacao seedlings. The most potential secondary metabolites are T. amazonicum LP3 and T. virens LP1 with respective disease suppression up to 81.8% and 63.2% or higher than and equivalent chemical fungicide (63.6%), and can increase plants height, number of leaves, and girth diameter.